Development and psychometric validation of the insect fear questionnaire for school-aged children in Iran - Arman Latifi; Mostafa Farahbakhsh; Saideh Yousefi; Somayeh Azimi; Mahasti Alizadeh; Tohid Jafari-Koshki; Aboozar Soltani; Sara Rahimi; Madineh Abbasi (PLoS ONE, 2026)
Background Insect-related fear (Entomophobia) is prevalent in children and affects their behavior and well-being, avoidance behaviors, and potentially hazardous practices such as inappropriate pesticide use. While many tools exist for measuring fear in adults, there is a lack of validated instruments for school-aged children. This study aimed to develop and validate a questionnaire assessing knowledge, entomophobia, behavior, and anxiety about insects among school-aged children in East Azerbaijan, Iran. Methods This psychometric study involved a multi-stage stratified random sampling design in East Azerbaijan Province, Iran. A researcher-made questionnaire, developed through expert consultation and literature review, was used. A total of 1,370 children participated. Content validity was quantified via CVR and CVI. Construct validity was assessed with exploratory factor analysis (EFA) and confirmatory factor analysis (CFA); EFA and reliability analyses (Cronbach’s alpha, item-total statistics) were performed in IBM SPSS Statistics 25, and CFA was conducted in AMOS 22. Temporal stability was evaluated by test–retest Intraclass Correlation Coefficients (ICC) over a two-week interval (n = 103). Result The finalized instrument comprises 32 items loading on four factors: knowledge, entomophobia, behavior, and personal fear/anxiety. EFA and CFA supported the four-factor model with excellent fit (CFI = 0.96, TLI = 0.95, RMSEA = 0.047, SRMR = 0.041). Internal consistency was acceptable (Cronbach’s α = 0.82), and test–retest reliability indicated good temporal stability (ICC = 0.81; 95% CI: 0.76–0.86). No meaningful floor or ceiling effects were observed. Conclusion The questionnaire demonstrates sound psychometric properties and is suitable for use in school settings to identify children with elevated insect-related fear or unsafe pesticide practices. Future work should examine criterion validity, measurement invariance across subgroups, and applicability in other cultural contexts.